Pemanfaatan Optimal Limbah: Inovasi dan Teknologi Pembuatan Briket dari Ampas Kopi dan Kulit Ari Kelapa - Syafri, Maulana Husein; Murnawan, Hery (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research aims to develop innovative briquette products using coffee grounds waste and coconut shells as the main raw materials. This waste has great potential to be used as an environmentally friendly alternative fuel, reduce organic waste, and provide added value economically. This research was conducted at Jokopi Indonesia and Ridho Abadi MSMEs, coffee grounds waste, which is produced from the espresso making process at Jokopi Indonesia, reaches an average of 330 kg per month, while coconut shell waste from Ridho Abadi MSMEs reaches 240 kg per month. Aiming to design an efficient briquette printing tool while calculating production costs and payback periods. By utilizing generally wasted waste, such as coffee grounds and coconut husks, the most optimal formulation is found at a ratio of 75% charcoal flour to 25% adhesive flour, resulting in briquettes with good burning quality and a long duration. The production capacity obtained reached 22.5 kg per day, with a yield of 2,813 briquettes, and the cost of production (HPP) of Rp8,762 per kg, providing a profit of Rp6,238 per kg. With a payback period of only 2 months, the investment in this briquette printing machine is considered feasible and has the potential to be further developed. Keywords: Briquette printing equipment, Coconut shells, Coffee grounds, Cost, Innovation, Production.